BIM Visual Programming Tools Applications in Infrastructure Projects: A State-of-the-Art Review - Collao, Jorge; Lozano-Galant, Fidel; Lozano-Galant, José Antonio; Turmo, Jose (Applied sciences, 2021)
The Building Information Modeling (BIM) methodology improves architectural and infrastructure projects by digitizing their processes throughout their life cycle stages, such as design, construction, management, monitoring, and operation. In recent years, the automation of these processes has been favored by the use of visual programming (VP) tools that have replaced conventional programming languages for visual schemes. The use of these tools in architectural projects is becoming increasing popular. However, this is not the case in infrastructure projects, for which the use of VP algorithms remains scarce. The aim of this work is to encourage both scholars and engineers to implement VP tools in infrastructure projects. For this purpose, this work reviews, for the first time in the literature, the state-of-the-art and future research trends of VP tools in infrastructure projects.